2021
DOI: 10.1111/jocd.14260
|View full text |Cite
|
Sign up to set email alerts
|

Skin cancer knowledge, attitudes, and practices among non‐medical skin care professionals: A narrative review of cross‐sectional and interventional studies

Abstract: Background Skin cancers are the most common malignancies in the United States. Total body skin examination by a physician, especially a dermatologist, is the gold standard for detecting suspicious lesions that may require further evaluation. Non‐medical professionals (NMPs) including massage therapists, estheticians, hairdressers, and cosmetologists have the unique opportunity to frequently examine their client's skin outside of a clinical setting. By evaluating their knowledge of and comfort with evaluation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Data regarding whether nonmedical professionals can screen accurately are lacking [11]. There is concern that training may cause overconfidence, leading to over-referral for benign lesions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Data regarding whether nonmedical professionals can screen accurately are lacking [11]. There is concern that training may cause overconfidence, leading to over-referral for benign lesions.…”
Section: Discussionmentioning
confidence: 99%
“…For example, "health-related" knowledge may encompass many topics including cosmetics or acne. Revisions to this wording may help further define comfort when Data regarding whether nonmedical professionals can screen accurately are lacking [11]. There is concern that training may cause overconfidence, leading to over-referral for benign lesions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent systematic review identified 16 studies done among non-medical professionals evaluating the knowledge of skin cancers among massage therapists, aestheticians, and hairdressers. 2 Roosta et al studied hairdressers' knowledge regarding melanomas. They noted that while almost 70% were likely to refer a client to seek medical attention, only 12% felt confident in their ability to identify these lesions.…”
mentioning
confidence: 99%